Sowing the seeds of sustainability: A sociological exploration of environmental sustainability within SME sector - Mohi ud Din; Aqeel Ahmad; Sarminah Samad; Sanghyeop Lee; Heesup Han (Climate Services)
This study provides a sociological investigation into the interconnected dynamics of green human resource management practices (GHRM), green transformational leadership (GTL), employees’ pro-environmental behaviors (EPB), green culture (GC), and environmental sustainability (ES) within the context of small and medium-sized enterprises (SMEs) in Lahore and Faisalabad, Pakistan. Utilizing a sample of 357 participants, comprising HR managers, leaders, and employees within SMEs, data were collected through self-report measures, and analysis was conducted using Smart PLS 4.0 software. The results underscore the positive impact of GHRM on EPB and ES through serial mediation of EPB and GC within SMEs, emphasizing the role of GHRM in cultivating pro-environmental attitudes among employees and enhancing overall environmental sustainability. However, the correlation between GHRM and the development of GC was found to be insignificant, suggesting the need to explore additional variables for fostering a green culture within organizations. Furthermore, the study reveals that EPB serves as a partial mediator between GHRM and both ES and GC. Notably, green transformational leadership (GTL) did not exhibit a significant moderating effect on the relationship between GHRM and EPB. This research provides valuable insights for organizations seeking to enhance environmental sustainability by promoting pro-environmental behaviors among employees and emphasizes the importance of cultivating a pervasive green culture to fully leverage the potential of GHRM practices. Despite acknowledging limitations such as a singular country focus and reliance on self-reported data, this study contributes to a deeper understanding of these phenomena within the sociocultural context of SMEs, thus augmenting the existing literature. Practical Implications: This study provides practical guidance for HR professionals and organizational leaders in the SME sector looking to implement strategic Green HRM interventions. By recognizing the positive impact of Green HRM practices on pro-environmental behavior and environmental sustainability, organizations can develop specific initiatives to encourage environmentally responsible behavior among their employees. Moreover, the research underscores the importance of cultivating a green organizational culture through the promotion of pro-environmental behavior and green initiatives. Organizations can use these insights to design awareness campaigns, training programs, and workshops that instill a sense of environmental responsibility, ultimately fostering a culture of sustainability. A significant practical implication of this study is the emphasis on employee engagement and empowerment in driving sustainability initiatives. By involving employees in decision-making processes and providing opportunities for them to participate in green projects, organizations can tap into their enthusiasm and commitment toward environmental sustainability. Additionally, the research explores Green Transformational Leadership as a moderator, opening avenues for leadership development programs that highlight environmentally conscious leadership practices. This approach allows organizations to nurture leaders who actively support and advocate for sustainability, positively influencing employees’ pro-environmental behavior. Furthermore, the study encourages SMEs to adopt and integrate environmentally sustainable practices into their business operations. Implementing eco-friendly processes, resource conservation measures and waste reduction initiatives can help align their business goals with environmental sustainability objectives. This not only benefits the environment but also leads to cost savings, increased efficiency, and enhanced organizational resilience. The practical implications extend to policymakers and regulatory bodies as well, emphasizing the importance of formulating environmentally friendly policies and regulations that incentivize and support Green HRM practices in the SME sector. This approach encourages organizations to voluntarily adopt sustainable practices, aligning them with national and global environmental targets. Another significant benefit highlighted in the research is that embracing sustainability practices can enhance an organization’s reputation as a socially responsible entity. Demonstrating commitment to environmental sustainability can attract environmentally conscious customers, investors, and partners, creating a positive impact on the organization’s brand image and market competitiveness. Moreover, the study fosters collaboration and knowledge sharing among organizations within the SME sector. This sharing of best practices, challenges, and successes in implementing Green HRM strategies promotes a collective effort towards sustainability. Lastly, the study underscores the importance of engaging various stakeholders, including employees, customers, suppliers, and local communities, in sustainability initiatives. Organizations can collaborate with these stakeholders to collectively address environmental challenges and develop innovative solutions. In a nutshell, by adopting Green HRM practices and fostering a culture of environmental responsibility, SMEs can achieve long-term sustainable growth. These practical implications equip organizations with actionable strategies to promote environmental sustainability, making a meaningful contribution towards a greener and more sustainable future for the SME sector and beyond.